Effect of two energy-protein supplements on the performance of cross-breed steers in feedlot - Assis, Airdem Gonçalves de; Souza, Ronaldo Mendes de; Villaça, Hermenegildo de Assis; Marcellino, Arnaldo (Pesquisa Agropecuaria Brasileira, 2014)
Sixteen cross-breed steers, thirty months old with an average liveweight of 350 kg, were used in a completely randomized design experiment, conducted at Coronel Pacheco, Minas Gerais State, Brazil, from June till October 1973, to compare two energy-protein supplements (molasses + urea and molasses + poultry litter) on the weight gain of steers under feedlot condition. The two lots were supplemented ad libifum with corn straw + paragrass (Brachiaria purpuracens) chopped and mixed with minerals. In the treatment molasses + poultry litter the results showed higher liveweight gain at lower cost. The average daily liveweight gains per steer during the experiment were 0.289 kg for those receiving molasses + urea, and 0.556 kg for those supplemented with molasses + poultry litter.